THE TRIPOD OF STAGNATION IN SOCIAL SCIENCES: INADEQUATE TEACHING METHODOLOGY, POOR DEVELOPMENT OF RESEARCH COMPETENCE AND ALL BUT DISSERTATION SYNDROME - Soto Acosta, Willy (2013)
Three closely interrelated elements in the Social Studies teaching and learning process are addressed in this paper: inadequate teaching strategies in methodology courses; poorly developed research skills in students, and the growing “All But Dissertation” (ABD) syndrome. As a final result, universities are preparing professionals who do not know how research. The above results from the objectification of the design methodology and the bureaucratic concept of research. The solution lies in having a research culture pervade the university curricula and in rethinking the teaching methodology.